2020
DOI: 10.1186/s12872-020-01644-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of regional left ventricular myocardial strain in patients with left anterior descending coronary stenosis using computed tomography feature tracking

Abstract: Background: Computed tomography feature tracking (CT-FT) has emerged as a valuable method for the assessment of cardiac function. However, no studies have investigated the usefulness of CT-derived assessments of left ventricular (LV) strain in coronary artery disease (CAD). Our aim was to evaluate regional LV systolic deformation in patients with left anterior descending coronary artery (LAD) stenosis using CT-FT. Methods: Seventy-six patients with LAD stenosis were enrolled. The patients were divided into fou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
0
7
0
2
Order By: Relevance
“…Upon conducting a multivariate regression analysis, age emerged as an independent risk factor for severe CAC, which is onsistent with previous research conducted at our centre 28 . Among the four main coronary branches, the LAD is the most commonly affected vessel in cardiovascular disease 29 , and exhibits the highest proportion of calcification, accounting for 67.21%. We have demonstrated that the factors influencing LAD calcification are comparable to those affecting the total CACS.…”
Section: Discussionmentioning
confidence: 99%
“…Upon conducting a multivariate regression analysis, age emerged as an independent risk factor for severe CAC, which is onsistent with previous research conducted at our centre 28 . Among the four main coronary branches, the LAD is the most commonly affected vessel in cardiovascular disease 29 , and exhibits the highest proportion of calcification, accounting for 67.21%. We have demonstrated that the factors influencing LAD calcification are comparable to those affecting the total CACS.…”
Section: Discussionmentioning
confidence: 99%
“…Non-smokers were defined as having less than 100 lifetime cigarettes, and the rest of the patients were categorized as regular smokers. Patients who drank alcohol were defined as having a positive history of alcohol consumption 7 . Family history of CAD was defined as a confirmed diagnosis of CAD in an immediate family member.…”
Section: Methodsmentioning
confidence: 99%
“…Quantifying CACs can aid in the prediction of future cardiovascular disease, and an increased CACs is directly related to increased disease risk 2 . The value of myocardial strain for diagnosis and risk stratification has been demonstrated in various cardiovascular diseases, such as severe aortic stenosis 3 , aortic valve replacement 4 , 5 , adult congenital heart disease 6 , isolated left anterior descending coronary stenosis 7 , and myocardial infarction 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Observou-se uma redução do strain longitudinal nos segmentos do território da artéria descendente anterior, a despeito de volumes diastólico, sistólico e FE normais. 446 …”
Section: O Papel Da Ressonância E Tomografia Cardíacas Na Avaliação D...unclassified
“…Lower LS was observed in segments related to the anterior descending artery, despite normal diastolic and systolic volumes and EF. 446 …”
Section: The Role Of Cardiac Resonance and Tomography In Strain Asses...mentioning
confidence: 99%